THE IMPACT OF THE EUROPEAN DIRECTIVE AGAINST FALSIFIED MEDICINES ON THE PHARMACEUTICAL WHOLESALERS IN BULGARIA - Krasimira Valcheva (Peytchinski Publishing, 2021)
In the last few decades, the problem with falsified medicine became a global threat that accounts for millions of human lives and billions of financial loses for the national health authorities and pharmaceutical industry. Different measures were developed to fight their uncontrolled spread but had only limited success. The resolution that united the pharmaceutical supply chain actors worldwide is the introduction of track-and-trace systems, based on product serialization and verification. The European Union also adopted this solution, and its official operation began in 2019. Each Member State has specifics that have to be accounted for in the national transposition process and should influence the system design and functionalities. In Bulgaria, the responsible authorities seriously delayed to adopt an adequate legal and regulatory framework to support its smooth operation. This created many problems for some of the key supply chain participants - the wholesalers. Since the European system is not a full track-and-trace solution, their role in the verification process is limited and left to the national authorities to decide how to regulate it. At present, more than one year after the launch of the system, the national bylaws that should regulate their activities with reference to the European policy are still not enforced. The wholesalers are left to align their operations in a regulatory vacuum that may compromise the effectiveness of the policy and lead to sanctions for noncompliance.